Lead right for your company's type how to connect your culture with your customer promise - Schneider, William E. (AMACOM, 2017)
This book explores the premise that every enterprise falls into one of four categories as dictated by their customer promise: customized (e.g. ad agency), predictable and dependable (e.g. utility company), benevolent (e.g. educational institution), and best in class (e.g. high-tech company like Apple). It serves to identify the failures of an enterprise and how to fix the problems when the enterprise falls apart.
Includes bibliographical references and index. - Description based on online resource; title from title page (viewed July 7, 2017)
Keywords: Leadership; Organizational behavior; Corporate culture; Customer relations; Comportement organisationnel; Culture organisationnelle